PENGEMBANGAN MEDIA PUZZLE KOSAKATA DALAM PEMBELAJARAN BAHASA JERMAN SISWA KELAS XI SMA - ROHMAH, LAILATUL (LATERNE, 2016)
Vocabulary Puzzle is a new medium that can facilitate students to understand new vocabulary in German. Based on the Needs questionnaire  of students who have been deployed in Language class XI SMAN 1 Krian, showed that 80.95% of students are interested in learning media, that it is formed a game that can help students where there are 76.19% of students had difficulty in understanding new vocabulary in German. Therefore it takes the media to help students. Problem Formulation of this research is "Does Vocabulary Puzzle feasible for learning German?" And the purpose of this research was to describe the feasibility Puzzle Vocabulary for learning the German language.  This type of research is the development of research based on the theory Sadiman. There are 6 stages in this study, namely (1) to analyze the needs of students, (2) formulate instructional purposes (instructional objective) with operational and distinctive, (3) formulating particles of matter in detail that supports the achievement of goals, (4) develop the tools measuring success, (5) writing the script media, (6) conduct trials / tests and revisions. The results of this research, validation media who got 68.75% of votes with the assessment criteria "Strong" and the results of the validation of 78.57% subject matter expert with the assessment criteria "Strong". If the results of the validation are averaged, then the overall result is 73.66% with the assessment criteria "Strong". Based on the validation results, we can conclude that the media Vocabulary Puzzle feasible to use in learning German. Keywords: media, puzzle, vocabulary.